Electrochemically anodized one-dimensional semiconductors: a fruitful platform for solar energy conversion. (17th April 2019) - Dai, Xiao-Cheng; Hou, Shuo; Huang, Ming-Hui; Li, Yu-Bing; Li, Tao; Xiao, Fang-Xing
Abstract: One-dimensional (1D) semiconductors have garnered considerable attention in solar energy harvesting and conversion since they possess a long axis to absorb incident light yet a short radial distance for fast separation of photogenerated charge carriers. Among the diverse 1D semiconductors, metal oxides arrays prepared by electrochemical anodization technique demonstrate unique structure merits for efficient charge separation and transfer; nevertheless, thus far, recent process on the photoelectrochemical (PEC) and photocatalytic applications of electrochemically anodized 1D semiconductors has not yet been elucidated. In this review, basic principle, classification, and developments of electrochemical anodization technique were systematically introduced. Great attention was paid to summarize the predominant 1D metal oxides arrays fabricated by anodization approach and their wide-spread photocatalytic and PEC applications. Moreover, modification strategies used for boosting the photocatalytic and PEC performances of 1D anodized metal oxides nanostructures were further comprehensively elucidated. Finally, future perspectives and challenges in triggering the future innovative ideas on fabricating a large variety of promising anodized semiconductor-based nanomaterials are envisaged. It is anticipated that our review could provide enriched information on the rational design and construction of electrochemically anodized 1D semiconductors for solar energy conversion.